Best management practices for sustainable reuse of treated wastewater - Choukr-Allah R.; Hamdy A. (Non-conventional water use: WASAMED project, 2005)
Agriculture application of recycled water is currently practiced in many countries in the Mediterranean basin to beneficially use the nutrients in recycled water for crop production and reduce the direct discharge of pollutants into inland and coastal waters. However, treated wastewaters are unique in composition, often associated with environmental and health risks. Thus, the effect of treated effluent on crops, soil and communities health must be considered carefully. Nevertheless, there is a need to study, the impact of treated wastewater on high value horticultural crops and on cereal crops. The aims of this paper is to review ten years of field research on the fate of the faecal coliforms and nutrients during the application of reclaimed wastewater to develop the best management for growing vegetables, flowers, and cereal crops species under Arid condition in the southern part of Morocco.
3. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2004/12/07-10, Cairo (Egypt)